Coffee and tea consumption, genotype-based CYP1A2 and NAT2 activity and colorectal cancer risk - Results from the EPIC cohort study - Dik, V; Bueno-De-Mesquita, H; Bueno-De-Mesquita, H; Bueno-De-Mesquita, H; Van Oijen, M; Siersema, P; Uiterwaal, C; Gils, V; Van Duijnhoven, F; Van Duijnhoven, F; Cauchi, S; Cauchi, S; et al. (2014)
Coffee and tea contain numerous antimutagenic and antioxidant components and high levels of caffeine that may protect against colorectal cancer (CRC). We investigated the association between coffee and tea consumption and CRC risk and studied potential effect modification by CYP1A2 and NAT2 genotypes, enzymes involved in the metabolization of caffeine. Data from 477,071 participants (70.2% female) of the European Investigation into Cancer and Nutrition (EPIC) cohort study were analyzed. At baseline (1992-2000) habitual (total, caffeinated and decaffeinated) coffee and tea consumption was assessed with dietary questionnaires. Cox proportional hazards models were used to estimate adjusted hazard ratio's (HR) and 95% confidence intervals (95% CI). Potential effect modification by genotype-based CYP1A2 and NAT2 activity was studied in a nested case-control set of 1,252 cases and 2,175 controls. After a median follow-up of 11.6 years, 4,234 participants developed CRC (mean age 64.7-±-8.3 years). Total coffee consumption (high vs. non/low) was not associated with CRC risk (HR 1.06, 95% CI 0.95-1.18) or subsite cancers, and no significant associations were found for caffeinated (HR 1.10, 95% CI 0.97-1.26) and decaffeinated coffee (HR 0.96, 95% CI 0.84-1.11) and tea (HR 0.97, 95% CI 0.86-1.09). High coffee and tea consuming subjects with slow CYP1A2 or NAT2 activity had a similar CRC risk compared to non/low coffee and tea consuming subjects with a fast CYP1A2 or NAT2 activity, which suggests that caffeine metabolism does not affect the link between coffee and tea consumption and CRC risk. This study shows that coffee and tea consumption is not likely to be associated with overall CRC. What's new? Coffee and tea contain numerous compounds that may protect against colorectal cancer (CRC). In this study of more than 475,000 participants over more than a decade, the authors investigated whether coffee or tea consumption is associated with an altered risk of developing CRC. They also asked whether genetic variations in two enzymes involved in caffeine metabolism (CYP1A2 and NAT2) might affect this risk. They conclude that neither consumption patterns, nor genetic differences in caffeine metabolism, appear to have a significant impact on CRC risk. © 2013 UICC.